Heterozygosity mapping for human dominant trait variants. - Imai-Okazaki, Atsuko; Li, Yi; Horpaopan, Sukanya; Riazalhosseini, Yasser; Garshasbi, Masoud; Mosse, Yael P; Zhang, Di; Schrauwen, Isabelle; Sharma, Aarushi; Fann, Cathy S J; Leal, Suzanne M; Lathrop, Mark; et al. (Hum Mutat, 2019)
Homozygosity mapping is a well-known technique to identify runs of homozygous variants that are likely to harbor genes responsible for autosomal recessive disease, but a comparable method for autosomal dominant traits has been lacking. We developed an approach to map dominant disease genes based on heterozygosity frequencies of sequence variants in the immediate vicinity of a dominant trait. We demonstrate through theoretical analysis that DNA variants surrounding an inherited dominant disease variant tend to have increased heterozygosity compared with variants elsewhere in the genome. We confirm existence of this phenomenon in sequence data with known dominant pathogenic variants obtained on family members and in unrelated population controls. A computer-based approach to estimating empirical significance levels associated with our test statistics shows genome-wide p-values smaller than 0.05 for many but not all of the individuals carrying a pathogenic variant.